Inspected shells at Hercules Port Ewen plant - Hercules Incorporated (1945)
Close-up view of inspected blasting cap shells ready to be loaded with an explosive charge and wired plug at the Hercules Powder Company plant in Port Ewen, New York. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) specialized in the manufacture of explosives and smokeless powders. During World War II, the company's Port Ewen plant produced a range of special detonators designed for military use.
Keywords: Explosives, Military; Detonators; Chemical industry; Propellants; Hercules Incorporated; World War (1939-1945); Military supplies; Corporations; Explosives; Defense industries